2006
DOI: 10.1089/apc.2006.20.335
|View full text |Cite
|
Sign up to set email alerts
|

To Take or Not to Take: Decision-Making About Antiretroviral Treatment in People Living with HIV/AIDS

Abstract: Knowledge is limited regarding decision-making about antiretroviral treatment (ART) from the patient's perspective. This substudy of a longitudinal study of psychobiologic aspects of long-term survival, conducted in 2003, compares the rationales of HIV-positive individuals (n = 79) deciding to take or not to take ART. Inclusion criteria were HIV/AIDS symptoms, or CD4 nadir less than 350, or viral load greater than 55,000. Those not meeting any criteria for receiving ART (2/2003 U.S. DHHS treatment guidelines) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
52
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 33 publications
(8 reference statements)
2
52
0
1
Order By: Relevance
“…Conversely, when spirituality is a source of meaning and growth and important in medical decision making, PLWH are often comforted by sharing beliefs with their clinician. [15][16][17][18][48][49][50]52 This is why clinicians should not defer the spiritual assessment to others, although providing spiritual interventions is best left to experts in spiritual care. 47 Koenig et al 47 dovetails our own experience that we as clinicians benefit too from bringing spirituality back to medicine by experiencing both greater work and patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, when spirituality is a source of meaning and growth and important in medical decision making, PLWH are often comforted by sharing beliefs with their clinician. [15][16][17][18][48][49][50]52 This is why clinicians should not defer the spiritual assessment to others, although providing spiritual interventions is best left to experts in spiritual care. 47 Koenig et al 47 dovetails our own experience that we as clinicians benefit too from bringing spirituality back to medicine by experiencing both greater work and patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…18 Third, spirituality plays a role in medical decision-making, adherence, quality of life, and clinician-patient relationship. 12,15,16,18,[48][49][50]52 Finally, it is important to assess the spiritual needs in order to identify people who may benefit from spiritual intervention. Potentially, spirituality-based interventions may aid in trauma treatment, as some experimental studies suggest.…”
Section: Discussionmentioning
confidence: 99%
“…S & D associated with HIV is a complex social process which interacts with and reinforces existing S & D associated with gender, race and poverty (Vanden Driessche et al, 2009). Numerous studies have documented attitudes of healthcare providers toward people living with HIV (PLHIV) (Chan et al, 2008, Kremer et al, 2006, Oku et al, 2013, Vanden Driessche et al, 2009. Although the literature characterizes the attitudes and behaviour of healthcare providers as positive and respectful, many studies also report poor communication between patients and healthcare providers (Chan et al, 2008, Kremer et al, 2006, which functions as a major barrier in providing proper care for these patients (Tawfik and Kinoti, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have also identified patient level barriers to the use of health services among people with substance abuse histories. For instance, research conducted with people living with HIV/AIDS found that individuals' decisions to take or not to take antiretroviral treatment were influenced by their perceptions about the treatment and alternative therapies, spirituality, and desire to avoid adverse side effects (Kremer, Ironson, Schneiderman, & Hautzinger, 2006). However, few studies have explored HCV-positive drug users' attitudes about HCV pharmacological therapy or the decisions they make when contemplating HCV treatment.…”
Section: Introductionmentioning
confidence: 99%